Arnon Rubin, Facts and Fictions about the Rescue of the Polish Jewry during the Holocaust - Agnieszka Haska (Zagłada Żydów)
Arnon Rubin, Facts and Fictions about the Rescue of the Polish Jewry during the Holocaust Tel Aviv Uniwersity Press, Tel Aviv 2003–2004